2023
DOI: 10.1002/smll.202207411
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Interface Polymerization with Micelle Mediated Assembly Towards Two‐Dimensional Mesoporous Carbon/CoNi for Advanced Lithium–Sulfur Battery

Abstract: Scheme 1. Schematic illustration of the synthesis process of the mNC-CoNi@rGO nanosheet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Pan et al reported that the adsorption free energy of H atoms (Δ G H* ) of bimetallic CoFe@N–C (−0.561 eV) is lower than that of Fe@N–C (−0.603 eV) and Co@N–C (−0.623 eV), which justifies the improvement in the HER activity . Previous works have demonstrated that the adsorption energy between lithium polysulfides (Li 2 S 4 ) and CoFe is −17.63 eV by DFT, which is much higher than that of single metals Co (−3.11 eV) and Fe (−2.68 eV) and other Co-based metallic alloys (CoNi: −4.24 eV). …”
Section: Introductionmentioning
confidence: 99%
“…Pan et al reported that the adsorption free energy of H atoms (Δ G H* ) of bimetallic CoFe@N–C (−0.561 eV) is lower than that of Fe@N–C (−0.603 eV) and Co@N–C (−0.623 eV), which justifies the improvement in the HER activity . Previous works have demonstrated that the adsorption energy between lithium polysulfides (Li 2 S 4 ) and CoFe is −17.63 eV by DFT, which is much higher than that of single metals Co (−3.11 eV) and Fe (−2.68 eV) and other Co-based metallic alloys (CoNi: −4.24 eV). …”
Section: Introductionmentioning
confidence: 99%
“…The typical synthesis of mesoporous metal oxides usually includes two main steps: the formation of mesostructure using a metal precursor and template (hard-template or soft-template) and the subsequent high-temperature crystallization as well as template removal. The hard-template method, similar to nanocasting, starts with infiltrating precursors into ordered mesoporous carbon or mesoporous silica (MCM-41, KIT-6, SBA-15) and then etching off the template to obtain the inverse mesostructure . Gu et al synthesized mesoporous ZrO 2 as a hard template, in which the surface-modified functional groups help to enhance the interaction between the template and the precursor.…”
Section: Introductionmentioning
confidence: 99%
“…27 A bimetallic CoNi-anchored ordered mesoporous N-doped carbon nanosheet sandwiched graphene (mNC-CoNi@rGO) was also shown to restrict the shuttle effect considerably. 28 With a smaller deposition barrier and less polarization, the catalytic efficiency of Co facilitated the deposition of Li 2 S on Co particles. As a result, at 0.2C, the Co and porous graphite (Co@GC-PC) electrode achieved a good specific capacity of 790 mAh g −1 after 220 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A nickel-plated sulfur nanocomposite with excellent conductivity and electrocatalytic activity toward polysulfides was created using an electroless plating technique. , With a high discharge capacity of 1008 mAh g –1 , the electroless nickel-plated sulfur nanocomposite presented good reaction kinetics and electrochemical reversibility . A bimetallic CoNi-anchored ordered mesoporous N-doped carbon nanosheet sandwiched graphene (mNC-CoNi@rGO) was also shown to restrict the shuttle effect considerably . With a smaller deposition barrier and less polarization, the catalytic efficiency of Co facilitated the deposition of Li 2 S on Co particles.…”
Section: Introductionmentioning
confidence: 99%